Expression and regulation by interferon of a double-stranded-RNA-specific adenosine deaminase from human cells: evidence for two forms of the deaminase. - Patterson, J B (1995)
A 6,474-nucleotide human cDNA clone designated K88, which encodes double-stranded RNA (dsRNA)-specific adenosine deaminase, was isolated in a screen for interferon (IFN)-regulated cDNAs. Northern (RNA) blot analysis revealed that the K88 cDNA hybridized to a single major transcript of approximately 6.7 kb in human cells which was increased about fivefold by IFN treatment. Polyclonal antisera prepared against K88 cDNA products expressed in Escherichia coli as glutathione S-transferase (GST) fusion proteins recognized two proteins by Western (immunoblot) analysis. An IFN-induced 150-kDa protein and a constitutively expressed 110-kDa protein whose level was not altered by IFN treatment were detected in human amnion U and neuroblastoma SH-SY5Y cell lines. Only the 150-kDa protein was detected in mouse fibroblasts with antiserum raised against the recombinant human protein; the mouse 150-kDa protein was IFN inducible. Immunofluorescence microscopy and cell fractionation analyses showed that the 110-kDa protein was exclusively nuclear, whereas the 150-kDa protein was present in both the cytoplasm and nucleus of human cells. The amino acid sequence deduced from the K88 cDNA includes three copies of the highly conserved R motif commonly found in dsRNA-binding proteins. Both the 150-kDa and the 110-kDa proteins prepared from human nuclear extracts bound to double-stranded but not to single-stranded RNA affinity columns. Furthermore, E. coli-expressed GST-K88 fusion proteins that included the R motif possessed dsRNA-binding activity. Extracts prepared either from K88 cDNA-transfected cells or from IFN-treated cells contained increased dsRNA-specific adenosine deaminase enzyme activity. These results establish that K88 encodes an IFN-inducible dsRNA-specific adenosine deaminase and suggest that at least two forms of dsRNA-specific adenosine deaminase occur in human cells.